Seeking long-lasting resistance to black node disease in common beans: Development of interspecific populations (2022)
There are no known common bean materials that are resistant to the black node disease (Boeremia noackiana [Allesch.] Aveskamp, Gruyter & Verkley). However, some studies have reported common bean genotypes that exhibit an intermediate reaction to this disease, but these materials lack stability in this trait. The secondary gene pool for beans (Phaseolus polyanthus Grenm.) has been screened since 1995 for this resistance. This population shows a varied response to this disease but lacks the characteristics of commercial grains. The study was carried out during 2017-2018 in Bogota under greenhouse conditions with interspecific crosses of commercial bean varieties (Phaseolus vulgaris L.) in Colombia and resistant genotypes from the ASC population of P. polyanthus, CIAT origin. To carry out the crosses, the hybridization technique with emasculation was followed, both in direct and reciprocal crosses. Low-efficiency viability in interspecific crosses from cytoplasmic genetic compatibility problems has been reported in different studies. However, in this study, the efficiency of the percentage of viable interspecific crosses increased significantly in the F1 populations and backcrosses, reaching 67%. Interspecific populations of Bacata × ASC 160 and Bacata × ASC 162 were formed with the seeds, which constituted the starting point for a breeding program for resistance to the black node disease in common beans using susceptible commercial cultivars.